2020
DOI: 10.1097/corr.0000000000001396
|View full text |Cite
|
Sign up to set email alerts
|

What Was the Change in Telehealth Usage and Proportion of No-show Visits for an Orthopaedic Trauma Clinic During the COVID-19 Pandemic?

Abstract: Background In response to the coronavirus disease 2019 (COVID-19) pandemic, the Centers for Medicare and Medicaid Services pledged payment for telehealth visits for the duration of this public health emergency in an effort to decrease COVID-19 transmission and allow for deployment of residents and attending physicians to support critical-care services. Although the COVID-19 pandemic has vastly expanded telehealth use, no studies to our knowledge have analyzed the implementation and success of teleh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 7 publications
2
53
1
Order By: Relevance
“…10 Another study of an orthopedic trauma clinic showed no significant difference in the rate of missed appointments when utilizing telehealth. 11 Overall, limited data are available regarding the impact of telehealth on missed appointments, especially in the primary care setting, indicating a need for future research in this area. Additional comparative studies may also evaluate no-show rates in a variety of clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…10 Another study of an orthopedic trauma clinic showed no significant difference in the rate of missed appointments when utilizing telehealth. 11 Overall, limited data are available regarding the impact of telehealth on missed appointments, especially in the primary care setting, indicating a need for future research in this area. Additional comparative studies may also evaluate no-show rates in a variety of clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging literature shows successful implementations of telehealth services due to COVID-19 across diverse medical settings. [15][16][17][18] Recent chronic pain expert consensus guidelines emphasize the need for continuity of care, highlighting the importance of telemedicine during the COVID-19 pandemic. 19,20 We did not know how the widespread implementation of telehealth in an integrative medicine clinic would impact the quality of care.…”
mentioning
confidence: 99%
“…In a previously telehealth-naive clinic, however, some authors have shown successful implementation of telehealth for a diverse orthopedic population with low mobility. 28 The physicians' perceptions of remote consultations were accessed by a web link survey, filled in, and sent back within 48 h after each consultation. The experience in our sample was positive, and the meetings were resolutive in most cases, requiring an in-person evaluation in less than 16% of cases.…”
Section: Discussionmentioning
confidence: 99%